Middle Meningeal Artery Embolization versus Surgery in Patients with Chronic Subdural Hematoma-No More Fence Sitting? - Dalibor Sila; Francisco Luis Casnati; Mária Vojtková; Philipp Kirsch; Stefan Rath; František Charvát (MDPI AG, 2023)
Background: Endovascular treatment of patients with chronic subdural hematoma using middle meningeal artery (MMA) embolization could become an alternative to surgical hematoma evacuation. The aim of the study was to compare methods and identify parameters to help determine the correct treatment modality. Methods: We retrospectively reviewed 142 cases conducted internally; 78 were treated surgically and 64 were treated using MMA embolization. We analyzed the treatment failure rate and complications, and using a binary logistic regression model, we identified treatment failure risk factors. Results: We found a comparable treatment failure rate of 23.1% for the surgery group and 21.9% for the MMA embolization group. However, in the MMA embolization group, 11 cases showed treatment failure due to early neurological worsening with a need for concomitant surgery. We also found a recurrence of hematoma in 15.4% of cases in the surgery group and 6.3% of cases in the MMA embolization group. Conclusion: Both modalities have their advantages; however, correct identification is crucial for treatment success. According to our findings, hematomas with a maximal width of <18 mm, a midline shift of <5 mm, and no acute or subacute (hyperdense) hematoma could be treated with MMA embolization. Hematomas with a maximal width of >18 mm, a midline shift of >5 mm, and no membranous segmentation could have better outcomes after surgical treatment.